Understanding the limit order book: Conditioning on trade informativeness - Héléna Beltran; Joachim Grammig; Albert J. Menkveld (University of Cologne, Centre for Financial Research (CFR), 2005)
Electronic limit order books are ubiquitous in markets today. However, theoretical models for limit order markets fail to explain the real world data well. Sandas (2001) tests the classic Glosten (1994) model for order book equilibrium and rejects it. We reconfirm this result for one of the largest European stock markets. We then relax one of the model's assumptions and allow the informational content of trades to change over time. Adapting Hasbrouck's (1991a,b) methodology to estimate time varying trade informativeness we find that it is a slowly mean reverting process. By conditioning on trade informativeness, we find support for the Glosten model's implication that books are more shallow during times of informative market orders. However, a high level of liquidity supply is committed up to an economically significant trade size volume, even when trade informativeness is high. This can be seen as a vindication of the open order book design which dispenses with dedicated market makers. We also find evidence for a market order trader population which is quite heterogenous with respect to price sensitivity.
Keywords: G10; 330; Informational content of trades; limit order book